The Foliar Ash Content in some Shorea robusta Trees of Different Quality Classes and its Relation with Soil Calcium in some forests of India - Puri, G. S. (Indian Forester, 1955)
The examination of foliar ash in I-IV quality classes of sal from different parts of the country have shown that ash content in these qualities is singnificantly different. Mineral content increases in qualities I-III and then shows a decrease in IV quality. A good negative correlation between the foliar ash and soil Ca has been found in some sal forests of M.P. These results tend to show that sal is a non-exacting species, showing its best development probably on non-calcareous and acidic soils. Too high alkalinity in the soil is unfavourable for its growth. These studies have definitely shown the possibility of analysing soil profiles by the analysis of foliage of trees growing on these areas. The analysis of soils from different depths is long, tedious and expensive, whereas foliar analysis is relatively easy and very much less expensive. It is yet too early to say whether we have really reached a stage where we can completely dispense with the analysis of the soil. However, there is a great possibility that with some further work we may be able to gain all the knowledge of plant environment that is required from foliar analysis alone and not have to analyse soils. These studies further show that the trees of different quality classes of sal constitute distinct physiological units and their management under one and the same system may not lead to good results in forest regeneration. Further application of the foliar analysis technique in forestry will be discussed later.